2000
DOI: 10.1046/j.1365-2486.2000.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic evaluation of photosynthetic acclimation at elevated CO2

Abstract: Summary Plants grown at elevated pCO2 often fail to sustain the initial stimulation of net CO2 uptake rate (A). This reduced, acclimated, stimulation of A often occurs concomitantly with a reduction in the maximum carboxylation velocity (Vc,max) of Rubisco. To investigate this relationship we used the Farquhar model of C3 photosynthesis to predict the minimum Vc,max capable of supporting the acclimated stimulation in A observed at elevated pCO2. For a wide range of species grown at elevated pCO2 under contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0
9

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 43 publications
6
93
0
9
Order By: Relevance
“…Among the parameters most associated with this decrease in the present study are maximum rate of carboxylation of rubisco, which presented significant reduction in Fepagro (experiment 1), Guapo (experiment 1) and Pinto (experiment 5), and carboxylation efficiency which presented a significant reduction in Fepagro cultivar (experiment 4) and Guapo cultivar (experiment 1) and the tendencies to reduction in Fepagro cultivar (experiment 1), Macotaço cultivar (experiment 1) and Pinto cultivar (experiment 5). Both maximum rate of carboxylation of rubisco, and carboxylation efficiency reflect the activity of rubisco in vivo (Rogers and Humphries 2000), and carboxylation reductions were considered the main factors responsible for impairment in photosynthesis by Pell et al (1994) and Guidi et al (2001). Guidi et al (2000), working with bean plants of Pinto cultivar, also found results that agree with the idea that the primary target of ozone are the enzymes involved in the Calvin cycle and, particularly, rubisco activity.…”
Section: Dry Mass Accumulationsupporting
confidence: 78%
“…Among the parameters most associated with this decrease in the present study are maximum rate of carboxylation of rubisco, which presented significant reduction in Fepagro (experiment 1), Guapo (experiment 1) and Pinto (experiment 5), and carboxylation efficiency which presented a significant reduction in Fepagro cultivar (experiment 4) and Guapo cultivar (experiment 1) and the tendencies to reduction in Fepagro cultivar (experiment 1), Macotaço cultivar (experiment 1) and Pinto cultivar (experiment 5). Both maximum rate of carboxylation of rubisco, and carboxylation efficiency reflect the activity of rubisco in vivo (Rogers and Humphries 2000), and carboxylation reductions were considered the main factors responsible for impairment in photosynthesis by Pell et al (1994) and Guidi et al (2001). Guidi et al (2000), working with bean plants of Pinto cultivar, also found results that agree with the idea that the primary target of ozone are the enzymes involved in the Calvin cycle and, particularly, rubisco activity.…”
Section: Dry Mass Accumulationsupporting
confidence: 78%
“…An enhanced rate of photosynthesis is ephemeral and presumably disappears because of nitrogen re-translocation to support new growth (Maier et al 2008). In addition, elevated atmospheric CO 2 leads to an increase in carbohydrate concentration and a reduction in the protein complement, especially Rubisco, which then reduces photosynthetic capacity and plant growth (Rogers and Humphries 2001). Although many studies have described the interaction eVects of elevated CO 2 and N supply, few of them have included a detailed analysis of dioecious plants' responses.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these processes respond, and may acclimate, to increases in [CO 2 ] and/or temperature [9]. At atmospheric [CO 2 ] of 395 ppm, net leaf level photosynthetic carbon assimilation (A) in herbaceous plants is mainly Rubisco-limited [10]. As atmospheric [CO 2 ] continues to increase [11], so too will the [CO 2 ] at the Rubisco catalytic site thereby stimulating A. Rubisco can also catalyze the oxygenation of RuBP leading to the energetically expensive photorespiration process [12,13].…”
Section: Introductionmentioning
confidence: 99%